Cyber PR Technology to Build Brand Awareness - M Solihat; F P Pratami (Universitas Komputer Indonesia, 2021)
The movement of tourism in Indonesia is increasingly showing progress every year, coupled with increasingly rapid technological advances resulting in technological innovations in the tourism sector. Information technology positively influences tourism sector, such as online ticket booking applications, especially during COVID-19 pandemics. This study aims to determine how online ticketing applications affect tourism and their impacts during a pandemic. One of them is about the influence of ticket and hotel booking application technology in the tourism sector, affecting tourists' behavior in traveling, and the condition of tourism today. This study method was distributing questionnaires to respondents. The analysis used statistics to determine the effect of online ticket booking applications on tourists' increase in Indonesia. This study indicates that this application makes it easy for tourists to travel, such as a hotel booking feature and purchasing tickets for tourist destinations online and increasing tourists' number. The majority of respondents stated that online applications help manage their trips during the pandemic.